Immortalization of patient-derived lip cells for establishing 3D lip models - Mansour, Farah; Parisi, Ludovica; Rihs, Silvia; Schnyder, Isabelle; La Scala, Giorgio C.; Aliu, Nijas; Katsaros, Christos; Degen, Martin (Frontiers in Cell and Developmental Biology, 2024)
The lips fulfill various critical physiological roles besides being viewed as a fundamental aesthetic feature contributing to the perception of health and beauty. Therefore, any lip injury, abnormality, or congenital malformation, such as cleft lip, needs special attention in order to restore proper lip function and aesthetics. To achieve this goal, a better understanding of the complex lip anatomy, function, and biology is required, which can only be provided by basic research endeavors. However, the absence of clinically relevant human lip cells and three-dimensional in vitro lip models, capable of replacing ethically questionable animal experimentations, remains a current limitation. To this end, we aimed to pioneer the introduction of immortalized healthy lip-and cleft lip-derived keratinocytes. Primary keratinocytes isolated from patients were immortalized by introducing the catalytic domain of telomerase, combined with targeted knockdown of the cell cycle inhibitor gene, p16 INK4A . We focused on validating the characteristics of the newly established cell lines, such as genetic stability and maintenance of key phenotypic keratinocyte features, by carrying out a robust comparison with their primary counterparts. Additionally, we generated three-dimensional lip models that can be used as convenient screening platforms for various assays in a multitude of lip-related research areas, including dermatology, skin care, wound healing, tissue engineering, and craniofacial anomalies. Collectively, the establishment of immortalized healthy lip and cleft lip-derived keratinocytes opens new avenues in studying lip abnormalities and provides unique tools for personalized medicine approaches beneficial to patients.